Customers' perception about concord's hospitality complex (Motel Atlantis) and its potential in the industry - Shafi, Tanvir Ibna (BRAC University, 2011)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2010.